Agro Food Wastes and Innovative Pretreatments to Meet Biofuel Demand in Europe. Issue 5 (12th March 2019) - Procentese, Alessandra; Raganati, Francesca; Olivieri, Giuseppe; Russo, Maria Elena; De La Feld, Marco; Marzocchella, Antonio
Abstract: The use of agricultural residues (AR) and agro‐food waste (AFW) as potential feedstocks for the production of second‐generation ethanol and butanol is reviewed. The maximum biofuel production rate from AR and AFW was estimated on the basis of the feedstock availability rate, the average composition, and the biofuel yields reported in the literature. According to the estimations, the contribution of ethanol and butanol to current European biofuel accounts could be 32 and 23 % if traditional pretreatments are applied, and 40 and 19 % if they are produced by innovative pretreatments, respectively. Finally, the analysis was applied to a local scenario (Campania, Italy), with a view to potential decentralized exploitation of AR and AFW. Abstract : Owing to the rising energy demand and the need to reduce greenhouse gas emissions, interest in biofuels is increasing. This review assesses the use of agricultural residues and agro‐food waste such as Brewer's spent grains (BSG) and coffee silverskin (CS) as potential feedstocks for the production of ethanol and butanol as biofuels in the European framework and for a local scenario (Campania, Italy).